Optical film, and optical barrier film, color conversion film, and backlight unit using same
By controlling the particle size distribution and using inorganic vapor-deposited thin film layers, the problem of haze instability caused by particle size differences in the light diffusing layer was solved, achieving performance uniformity and durability of optical films and color conversion films.
Patent Information
- Application Number
- CN202511039218.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2016-12-06
- Filing Date
- 2017-10-02
- Publication Date
- 2025-11-04
AI Technical Summary
In the prior art, the particle size difference of the orthogonal spherical particles in the light diffusing layer is large, which leads to unstable haze values, affects the in-plane difference of the optical film, and the thickness non-uniformity of the optical film affects the performance of the color conversion film.
By controlling the average particle size of the microparticles to be between 0.5 μm and 10.0 μm, and with the standard deviation of the particle size being less than half of the average particle size, a coating is formed using a wet coating process with adhesive resin and microparticles. This is combined with an inorganic vapor-deposited thin film layer and a barrier layer to suppress the aggregation and detachment of microparticles, thereby controlling the thickness and hardness of the coating.
This achieves a small in-plane difference in haze value, suppresses adhesion and damage between the coating and other components, and improves the performance stability and durability of optical films, optical barrier films and color conversion films.
Smart Images

Figure CN120891571A_ABST
Abstract
Description
[0001] This patent application is a divisional application of patent application No. 2017800749252, filed on October 2, 2017, entitled "Optical Film, and Optical Barrier Film, Color Conversion Film, and Backlight Unit Each Using the Same". TECHNICAL FIELD
[0002] The present disclosure relates to an optical film, and an optical barrier film, a color conversion film, and a backlight unit each using the same. BACKGROUND
[0003] Various optical films are used in electronic devices such as liquid crystal displays. The invention described in Patent Literature 1 relates to a light-diffusing sheet for illuminating devices, light-emitting signs, back-projection screens, liquid crystal display screens, and the like. The light-diffusing sheet described in Patent Literature 1 has a light-diffusing layer containing spherical particles composed of polymethyl methacrylate.
[0004] PRIOR ART DOCUMENTS
[0005] PATENT LITERATURE
[0006] Patent Literature 1: Japanese Patent No. 3790571 SUMMARY
[0007] PROBLEMS TO BE SOLVED BY THE INVENTION
[0008] However, in the invention described in Patent Literature 1, when the particle size of the spherical particles contained in the light-diffusing layer greatly differs, or the spherical particles coagulate to form secondary particles, or the dispersibility in the light-diffusing layer is insufficient, the haze value, which is an index of light diffusion, easily differs, and there is room for improvement in this regard.
[0009] An object of the present disclosure is to provide an optical film in which the in-plane difference in the haze value is sufficiently small, and an optical barrier film, a color conversion film, and a backlight unit each using the same.
[0010] MEANS FOR SOLVING THE PROBLEMS
[0011] One aspect of the present disclosure provides an optical film. The optical film has a first film substrate and a coating layer formed on the first film substrate, and the coating layer contains a binder resin and microparticles, the average particle diameter of the microparticles being 0.5 μm or more and 10.0 μm or less and the standard deviation of the particle diameter being less than 1 / 2 of the average particle diameter. According to the optical film, the particle size difference of the microparticles in the coating layer is sufficiently small, and more specifically, the average particle diameter is in a predetermined range (0.5 μm or more and 10.0 μm or less) and the standard deviation of the particle diameter is less than 1 / 2 of the average particle diameter, and thus, it is possible to provide an optical film having a coating layer in which the in-plane difference in the haze value is sufficiently small. More specifically, it is possible to solve the following problems.
[0012] In the production process of the optical film, for example, a coating layer can be formed on the first film substrate by wet coating. Wet coating is a method of forming a coating layer by a process of applying a coating liquid containing a binder resin and fine particles dispersed therein to the first film substrate. If the difference (standard deviation) in the particle size of the fine particles contained in the coating liquid is large, the particle size distribution of the fine particles observed in the coating layer after film formation also inevitably becomes large. On the other hand, even if the designed value of the particle size of the fine particles is a value in which the difference is sufficiently small, if the dispersibility of the fine particles in the binder resin is insufficient due to aggregation of the fine particles or the like, the particle size distribution of the fine particles observed in the coating layer after film formation becomes larger than the designed value of the particle size of the fine particles. According to the research of the present inventor, there is a problem that when the difference in the particle size of the fine particles contained in the coating layer is large, the light diffusion property (haze value) exhibited by the coating layer is unstable (the in-plane difference in the optical film becomes large).
[0013] Not only the above problem exists, but also in the production process of a color conversion film using an optical film, the thickness of the optical film (and the thickness of an optical barrier film containing the same) also affects the coating thickness of a color conversion material, and thus also greatly affects the performance of the color conversion film. More specifically, when the difference in the particle size of the fine particles contained in the optical film is large, it becomes a state in which, for example, a large particle protrudes from the surface of the binder resin, and this portion can become the maximum thickness of the optical film, and thus this becomes a cause of a difference in the performance of the color conversion film. The optical film according to the present disclosure can sufficiently solve these problems.
[0014] From the viewpoint of suppressing the detachment (powdering) of the fine particles from the coating layer, the arithmetic mean roughness Ra of the coating layer 14 is preferably 0.4 μm or less.
[0015] From the viewpoint of suppressing the damage of the coating layer by other components (for example, a prism sheet), or suppressing the damage of other components (for example, a light guide plate) by the coating layer, it is preferable that the hardness of the coating layer be in the range of H to 2H in terms of pencil hardness. The difference in the particle size of the fine particles in the coating layer is sufficiently small, and thus the difference in the pencil hardness in the coating layer is also sufficiently small.
[0016] The hardness of the fine particles is preferably 100 or less in terms of the Rockwell R hardness scale. By the hardness of the fine particles being in the above range, the damage of the coating layer and other components can be suppressed. The surface resistance of the coating layer is preferably 1.0 x 10 13 Ω / □. By the surface resistance of the coating layer being in the above range, the antistatic property can be appropriately imparted to the coating layer.
[0017] The present disclosure provides an optical barrier film of a first mode. The optical barrier film includes a barrier layer and the optical film, the barrier layer being formed on a surface of the optical film on the first film substrate side. The present disclosure provides an optical barrier film of a second mode. The optical barrier film includes a barrier composite layer including a second film substrate and a barrier layer, and the optical film, the barrier composite layer being formed on a surface of the optical film on the first film substrate side. The optical barrier film of these embodiments includes the optical film, and thus, the problem can be solved, and adhesion of the optical barrier film to other components in contact therewith and damage to the coating layer and other components can be suppressed.
[0018] The barrier layer preferably includes an inorganic vapor deposition thin film layer composed of a silicon oxide represented by SiOx (1.0≦x≦2.0). By including the inorganic vapor deposition thin film layer in the barrier layer, the barrier performance of the optical barrier film tends to be improved. x (1.0≦x≦2.0). By including the inorganic vapor deposition thin film layer in the barrier layer, the barrier performance of the optical barrier film tends to be improved.
[0019] One aspect of the present disclosure provides a color conversion film. The color conversion film includes a color conversion layer and two protective films configured to sandwich the color conversion layer, at least one of the two protective films being the optical barrier film, the optical barrier film being configured with the coating layer facing the opposite side of the color conversion layer. The color conversion film includes the optical barrier film, and thus, the problem can be solved, and damage to a light guide plate, for example, constituting a backlight unit, can be suppressed even if the light guide plate overlaps. In addition, damage to the barrier layer itself can be suppressed, and thus, air and water vapor can be appropriately reduced from invading the color conversion layer, and the color conversion performance of the color conversion film can be maintained for a long period of time.
[0020] One aspect of the present disclosure provides a backlight unit. The backlight unit includes a light source, a light guide plate, and the color conversion film configured on the light guide plate, the color conversion film being configured with the coating layer in contact with the light guide plate. The backlight unit includes the color conversion film, and thus, the problem can be solved, and damage to the light guide plate in contact with the color conversion film can be suppressed. In addition, damage to the barrier layer itself can be suppressed, and thus, air and water vapor can be appropriately reduced from invading the color conversion layer, and good white light can be obtained from the backlight unit for a long period of time.
[0021] Effects of Invention
[0022] According to the present disclosure, an optical film having a sufficiently small in-plane difference in haze value, and an optical barrier film, a color conversion film, and a backlight unit using the same are provided. BRIEF DESCRIPTION OF DRAWINGS
[0023] [ Figure 1 ] Figure 1 is a schematic cross-sectional view of an optical film according to one embodiment of the present disclosure.
[0024] [ Figure 2 ] Figure 2 is a schematic cross-sectional view of an optical barrier film according to a first embodiment of the present disclosure.
[0025] [ Figure 3 ] Figure 3 is a schematic cross-sectional view of an optical barrier film according to a second embodiment of the present disclosure.
[0026] [ Figure 4 ] Figure 4 is a schematic cross-sectional view of an optical barrier film according to a third embodiment of the present disclosure.
[0027] [ Figure 5 ] Figure 5 is a schematic cross-sectional view of an optical barrier film according to a fourth embodiment of the present disclosure.
[0028] [ Figure 6 ] Figure 6 is a schematic cross-sectional view of a color conversion film according to an embodiment of the present disclosure.
[0029] [ Figure 7 ] Figure 7 is a schematic cross-sectional view of a backlight unit according to an embodiment of the present disclosure.
[0030] [ Figure 8 ] Figure 8 (a) is an image shown after enlarging the coating of the optical film of Example 2 with an optical microscope, Figure 8 (b) is an image shown after further enlarging the particles surrounded by the circle in (a). Figure 8 (a) is an image shown after further enlarging the particles surrounded by the circle in (a).
[0031] [ Figure 9 ] Figure 9 is an optical microscope image showing a portion of the coating of the optical film of Example 2 that is considered to be removed as a particle. DETAILED DESCRIPTION
[0032] Hereinafter, embodiments of the present disclosure will be explained in detail with reference to the attached drawings. Note that,
[0033] In the drawings, the same or similar elements are marked by the same reference numerals, and repetitive explanations are omitted.
[0034] [Optical Film]
[0035] Figure 1 is a schematic cross-sectional view of an optical film according to an embodiment of the present disclosure. Figure 1 In the embodiment, the optical film 10 includes a first film substrate 12 and a coating layer 14 formed on the first film substrate 12.
[0036] (Coating Layer)
[0037] The coating layer 14 is a layer having a function of diffusing light, and is also sometimes referred to as a "matt layer" or the like. The coating layer 14 contains the fine particles 18, and at least a part of the fine particles 18 protrude on the surface of the coating layer 14 on the side opposite to the first film substrate 12. By at least a part of the plurality of fine particles 18 in the coating layer 14 protruding on the surface of the coating layer 14, the coating layer 14 can have a concavo-convex shape on the surface. By the coating layer 14 having a concavo-convex shape, that is, having a concavo-convex surface 14A on the surface on the side opposite to the first film substrate 12, in the case where another member is laminated on the surface of the coating layer 14 of the optical film 10, it is possible to suppress adhesion (sticking) to the other member. Note that, by "protrude" of the fine particles 18 on the surface of the coating layer 14, it is meant that at least a part of the area of the surface of the fine particles 18 is located outside the reference surface of the surface of the coating layer 14 where the fine particles 18 are not present. The surface of the protruding fine particles 18 can be exposed, or can be covered with an adhesive resin or the like described later.
[0038] The average particle diameter of the fine particles 18 is 0.5 μm or more and 10.0 μm or less, preferably 1.0 μm or more and 10.0 μm or less, and more preferably 2.0 μm or more and 8.0 μm or less. When the average particle diameter of the fine particles 18 is 0.5 μm or more, it is easy to suppress the occurrence of adhesion between the coating layer 14 and another member in contact therewith. On the other hand, when the average particle diameter of the fine particles 18 is 10.0 μm or less, it is easy to control the concavo-convex shape of the surface of the coating layer 14 to be small using the protruding fine particles 18, and thus it is easy to suppress damage to another member in contact with the concavo-convex surface 14A of the coating layer 14.
[0039] The standard deviation of the particle diameter of the fine particles 18 is lower than 1 / 2, preferably lower than 1 / 3, and more preferably lower than 1 / 4, of the average particle diameter of the fine particles 18. When the value is lower than 1 / 2, it is possible to sufficiently reduce the in-plane variation in the haze value (haze) in the coating layer 14. In addition, the standard deviation of the particle diameter of the fine particles 18 being lower than 1 / 2 of the average particle diameter of the fine particles 18 means that the number of particles having a particle diameter that is excessively large is sufficiently small, and thus it is possible to sufficiently suppress the problem of chalking (powdering) and appearance caused by particles having a large particle diameter detaching after coating during the production of the optical film 10. Furthermore, in the case where the coating layer 14 is formed by wet coating, it is possible to control the thickness of the coating layer 14 by adjusting the coating amount, and thus it is advantageous in that it is easy to form a coating layer 14 having a desired thickness. Note that, from the viewpoint of the production technology of the fine particles 18, the lower limit of the value is about 1 / 5.
[0040] As described above, the detachment (powdering) of the fine particles from the coating layer 14 can be sufficiently suppressed as long as the number of particles having a particle size that is too large is reduced in the coating layer 14. Whether or not the number of the larger particles is large (whether or not the powdering is likely to occur) in the coating layer 14 can be grasped by measuring the arithmetic average roughness Ra of the coating layer 14. From the viewpoint of sufficiently suppressing the powdering, the arithmetic average roughness Ra of the coating layer 14 is preferably 0.4 μm or less, more preferably 0.3 μm or less.
[0041] The pencil hardness of the coating layer 14 is preferably in the range of H to 2H. The particle size difference of the fine particles 18 included in the coating layer 14 is sufficiently small, and thus the difference in the pencil hardness of the coating layer 14 can also be sufficiently small. By the pencil hardness of the coating layer 14 being H or more, the coating layer 14 can be suppressed from being damaged by other members (for example, a prism sheet). On the other hand, by the pencil hardness of the coating layer 14 being 2H or less, the coating layer 14 can be suppressed from damaging other members (for example, a light guide plate). The pencil hardness referred to herein is a value measured in accordance with JIS K5600-5-4: 1999 (ISO / DIS 15184: 1996) "Scratch hardness (pencil method)", and refers to a value measured with a load of 500 g applied to the tip of a pencil.
[0042] The thickness of the coating layer 14 is preferably in the range of 0.5 μm to 30 μm. In the present specification, the thickness of the coating layer 14 is assumed to be an average thickness including the concavo-convex shape. The thickness of the coating layer 14 is measured by the mass method according to JIS K5600. When the coating layer 14 has a thickness in this range, the fine particles 18 are likely to protrude on the surface of the coating layer 14, and the concavo-convex surface 14A is likely to be formed on the coating layer 14.
[0043] The content of the fine particles 18 in the coating layer 14 is preferably in the range of 2 to 80% by mass, more preferably in the range of 5 to 50% by mass, based on the total amount of the coating layer 14. When the content of the fine particles 18 is 2% by mass or more, the fine particles 18 are likely to protrude on the surface of the coating layer 14, and the generation of the adhesion of the coating layer 14 to other members in contact therewith is likely to be suppressed. On the other hand, when the content of the fine particles 18 is 80% by mass or less, the damage of other members in contact with the concavo-convex surface 14A of the coating layer 14 is likely to be suppressed.
[0044] The proportion of the fine particles 18 protruding on the surface of the coating layer 14 in the fine particles 18 included in the coating layer 14 is preferably in the range of 10 to 100%, more preferably in the range of 50 to 100%. When the proportion of the protruding fine particles 18 is 10% or more, the generation of the adhesion is likely to be suppressed.
[0045] The hardness of the fine particles 18 is 100 or less on the Rockwell R hardness scale, and preferably 90 or less. When the hardness of the fine particles 18 is 100 or less on the Rockwell R hardness scale, damage to other components that come into contact with the concave-convex surface 14A of the coating layer 14 by the protruding fine particles 18 is easily suppressed. In addition, from the same viewpoint, the hardness of the fine particles 18 is preferably 50 or less on the Rockwell M hardness scale.
[0046] As for the fine particles 18, there is no particular limitation as long as the Rockwell hardness is within the above range, and the fine particles 18 can be inorganic fine particles or organic fine particles. In order to set the Rockwell hardness within the above range, the fine particles 18 are preferably organic fine particles. As the organic fine particles, for example, polyolefin resins such as polypropylene; polyamide resins such as nylon; acryl urethane resins; styrene resins; urethane resins; benzoguanamine resins; silicone resins; acrylic resins; and the like can be given. The fine particles 18 are more preferably at least one organic fine particle selected from the group consisting of polyolefin resins, polyamide resins, urethane resins, and silicone resins, and further preferably polypropylene resin particles or urethane resin particles. In addition, when the fine particles 18 are organic fine particles, the fine particles 18 easily become spherical particles, and in addition, the shape easily becomes a smooth concave-convex shape. The fine particles 18 can be used alone or in combination with a plurality of types. Note that, within a range that does not impair the effects of the present disclosure, the coating layer 14 can contain particles other than the fine particles 18, which have a Rockwell hardness that is not within the above range.
[0047] The coating layer 14 can contain an electrically conductive material. When the coating layer 14 contains an electrically conductive material, the surface resistance of the coating layer 14 tends to be reduced. The surface resistance of the coating layer 14 is preferably 1.0 x 10 13 Ω / □ or less. When the surface resistance of the coating layer 14 is 1.0 x 10 13 Ω / □ or less, the antistatic properties of the coating layer 14 can be appropriately imparted, and thus, the attachment or mixing of dust and the like to the coating layer 14 tends to be reduced. Therefore, in the manufacturing process of the backlight unit and the like, damage to the coating layer 14 or other components due to dust tends to be reduced. As the electrically conductive material, for example, quaternary ammonium salt compounds, electrically conductive polymers, metal oxides, and the like can be given. The electrically conductive material can be used alone or in combination with a plurality of types.
[0048] The quaternary ammonium salt compound is a compound having a quaternary ammonium salt as a functional group within a molecule, for example, a (meth)acrylate compound having a quaternary ammonium salt as a functional group within a molecule. The (meth)acrylate compound having a quaternary ammonium salt as a functional group within a molecule may, for example, be a (meth)acrylate of a polyol having a quaternary ammonium salt as a functional group within a molecule (i.e., a quaternary ammonium salt (meth)acrylate compound), or a reactant of a diisocyanate, a polyol, and a hydroxyalkyl (meth)acrylate of the like (i.e., a quaternary ammonium salt urethane (meth)acrylate compound), and the like. In addition, a polyether resin having an acrylate functional group, a polyester resin, an epoxy resin, an alkyd resin, a spiroacetal resin, a polybutadiene resin, a polysulfide polyene resin, and the like can also be used as the quaternary ammonium salt compound. The quaternary ammonium salt has a quaternary ammonium cation and an anion. As the anion of the quaternary ammonium salt, for example, Cl - , Br - , I - , F - , HSO4 - , SO4 2- , NO3 - , PO4 3- , HPO4 2- , H2PO4 - , SO3 - , OH - , and the like can be given.
[0049] The electrically conductive polymer can be composed of one or a mixture of two or more selected from the group consisting of polyacetylene, polyaniline, polythiophene, polypyrrole, polyphenylene sulfide, poly(1,6-heptadiyne), polyphenylene (poly-p-phenylene), poly-p-phenylene sulfide, polyphenylacetylene, poly(2,5-thiophene), and derivatives thereof.
[0050] As the metal oxide, for example, zirconium oxide, antimony-containing tin oxide (ATO), phosphorus-containing tin oxide (PTO), tin-containing indium oxide, aluminum oxide, cerium oxide, zinc oxide, aluminum-containing zinc oxide, tin oxide, lithium salt, antimony-containing zinc oxide, indium-containing zinc oxide, and the like can be given.
[0051] The particle diameter of the electrically conductive material is, for example, 500 nm or less, and preferably 100 nm or less. When the particle diameter of the electrically conductive material is 500 nm or less, even if a particle having a Rockwell hardness not within the above range is used as the electrically conductive material, the damage suppression effect is not hindered, and it tends to be possible to reduce the surface resistance of the coating layer 14. The content of the electrically conductive material in the coating layer 14 is appropriately set according to the kind of the electrically conductive material so that the surface resistance of the coating layer 14 becomes a desired range. Note that from the viewpoint of the adhesion of the coating layer 14 to the first film substrate 12, the content of the electrically conductive material in the coating layer 14 can be 30% by mass or less.
[0052] Figure 1 In the case where the coating layer 14 further contains the binder resin 16, the binder resin 16 is a resin excellent in optical transparency, and can be a molded body of a thermoplastic resin, or a cured product of a thermally curable resin or a radiation curable resin. As the resin constituting the binder resin, for example, a polyester-based resin, an acrylic-based resin, an acrylic urethane-based resin, a polyester acrylate-based resin, a polyurethane acrylate-based resin, an epoxy acrylate-based resin, a urethane-based resin, an epoxy-based resin, a polycarbonate-based resin, a cellulose-based resin, an acetal-based resin, a polyvinyl-based resin, a polystyrene-based resin, a polyamide-based resin, a polyimide-based resin, a melamine-based resin, a phenol-based resin, a silicone-based resin, or the like can be given.
[0053] In the case where the binder resin 16 is a cured product of a thermally curable resin, the cured product of the thermally curable resin can be a reaction product of the thermally curable resin and a curing agent. The binder resin 16 is preferably a cured product of a thermally curable resin having a hydroxyl group and an isocyanate curing agent. In this case, isocyanate groups of the isocyanate curing agent react with the hydroxyl group of the thermally curable resin, and the thermally curable resin and the isocyanate curing agent can be cured.
[0054] From the viewpoint of being able to crosslink the polyol resin, the isocyanate curing agent is preferably an isocyanate curing agent having two or more isocyanate groups, and more preferably a diisocyanate curing agent having two isocyanate groups. As the diisocyanate curing agent, an aliphatic diisocyanate such as hexamethylene diisocyanate or xylylene diisocyanate, an aromatic diisocyanate such as toluene diisocyanate or diphenylmethane diisocyanate, and a derivative thereof can be given.
[0055] The coating layer 14 is formed by, for example, applying a coating composition to the first film substrate 12, and drying and curing or molding the coating film as necessary. The coating composition is composed of, for example, the above-described microparticles 18, a conductive material, and a thermoplastic resin, a thermally curable resin, or a radiation curable resin. The coating composition can further contain a solvent, a photopolymerization initiator, a leveling agent, or a slip agent. The coating of the coating composition is performed using, for example, a roll coater, a reverse roll coater, a gravure coater, a microgravure coater, a knife coater, a bar coater, a wire bar coater, a die coater, or a dip coater.
[0056] In the case where the coating composition contains a solvent, the coating film is dried by heating or air blowing. The drying temperature when heating is, for example, about 60 to 100°C, and the drying time is, for example, about 10 seconds to 10 minutes. By the above-described drying, a large amount of the solvent is removed from the coating film.
[0057] In the case where the coating composition contains a thermally curable resin, the coating film after drying is subjected to heating. The heating temperature is, for example, about 50 to 100°C, and the heating time is, for example, about 12 hours to 3 days. By the above heating, the coating film is cured.
[0058] In the case where the coating composition contains a radiation curable resin, the coating film after drying is subjected to radiation. The radiation can be, for example, ultraviolet rays or electron beams. The ultraviolet rays are generated from, for example, light sources such as high-pressure mercury lamps, low-pressure mercury lamps, super-high-pressure mercury lamps, metal halide lamps, carbon arc lamps, and xenon arc lamps. In addition, the electron beams are generated from, for example, various electron beam accelerators such as Cockroft-Walton type, Van De Graft type, resonance transformer type, insulated-core transformer type, linear type, Dynamitron type, and high-frequency type. By the above radiation, the coating film is cured.
[0059] (First film substrate)
[0060] The first film substrate 12 can be, for example, an organic polymer film. The first film substrate 12 is preferably transparent, and specifically, the total light transmittance of the first film substrate 12 is preferably 80% or more. As the first film substrate 12, for example, a polyolefin-based film substrate such as polyethylene or polypropylene, a polyester-based film substrate such as polyethylene terephthalate or polyethylene naphthalate, a cellulose-based film substrate such as triacetyl cellulose, diacetyl cellulose, or cellophane, a polyamide-based film substrate such as 6-nylon or 6,6-nylon, an acrylic-based film substrate such as polymethyl methacrylate, a polystyrene-based film substrate, a polyvinyl chloride-based film substrate, a polyimide-based film substrate, a polyvinyl alcohol-based film substrate, a polycarbonate-based film substrate, and an ethylene vinyl alcohol-based film substrate can be used.
[0061] The thickness of the first film substrate 12 is preferably, for example, 5 μm or more and 300 μm or less. When the thickness of the first film substrate 12 is 5 μm or more, the strength of the first film substrate 12 is improved, and, for example, the handling of the first film substrate 12 tends to become easy in a back light unit manufacturing process or the like. On the other hand, when the thickness of the first film substrate 12 is 300 μm or less, the handling of the first film substrate 12 tends to become easy in a film formation process of a roll-to-roll system.
[0062] [Optical barrier film]
[0063] (First embodiment)
[0064] Figure 2 is a schematic cross-sectional view of an optical barrier film according to the first embodiment of the present disclosure. Figure 2In the optical barrier film 20A, the optical barrier film 20A has the barrier layer 24 and the optical film 10. The barrier layer 24 is formed on the side of the first film substrate 12 of the optical film 10. That is, the optical barrier film 20A can have the first film substrate 12, the coating layer 14 formed on one surface of the first film substrate 12, and the barrier layer 24 formed on the other surface of the first film substrate 12. As described above, the in-plane difference in the haze value of the coating layer 14 is sufficiently small, and thus the in-plane difference in the haze value of the optical barrier film 20A can also be sufficiently small.
[0065] The optical film 10 has a concavo-convex shape on the surface on the side of the coating layer 14, that is, has the concavo-convex surface 14A. Thus, in the case where the other member is laminated on the surface of the optical film 10 (coating layer 14) of the optical barrier film 20A, the adhesion to the other member can be suppressed. In addition, even if the optical barrier film 20A is laminated with the other member, the coating layer 14 and the other member in contact with the concavo-convex surface 14A of the coating layer 14 can be prevented from being damaged by the protruding particles 18. Note that the barrier layer 24 can also be formed on the surface of the first film substrate 12 of the optical film 10 via an adhesion layer.
[0066] The barrier layer 24 is a layer capable of blocking the invasion of a gas. The barrier layer 24 preferably contains an inorganic thin film layer. The inorganic thin film layer contains an inorganic compound, and preferably contains a metal or a metal oxide. As the metal, for example, aluminum, copper, and silver can be given. In addition, the metal oxide can be, for example, at least one metal oxide selected from the group consisting of yttrium tantalum oxide, aluminum oxide, silicon oxide, and magnesium oxide, and from the viewpoint of being inexpensive and having excellent barrier properties against the invasion of water vapor and the like, the silicon oxide is preferred. Preferably, the silicon oxide is SiO x is represented by the formula, and x in the formula is 1.5 or more and 2.0 or less. When x is 1.5 or more, more preferably 1.7 or more, the transparency tends to be improved. In addition, when x is 2.0 or less, the barrier properties tend to be excellent. The inorganic thin film layer is formed, for example, by a vapor deposition method or a sputtering method, and is preferably an inorganic vapor deposition thin film layer formed by a vapor deposition method. The thickness of the inorganic thin film layer is preferably 10 to 300 nm, and more preferably 20 to 100 nm. By making the thickness of the inorganic thin film layer 10 nm or more, a uniform film is easily obtained, and the gas barrier properties tend to be easily obtained. On the other hand, by making the thickness of the inorganic thin film layer 300 nm or less, the inorganic thin film layer can be kept soft, and has the tendency that it is difficult to cause cracks and the like due to external forces such as bending and stretching after film formation.
[0067] The barrier layer 24 can also contain a gas barrier coating layer. The gas barrier coating layer is preferably formed from a composition containing at least one selected from the group consisting of metal alkoxides represented by the following formula (1) and hydrolyzates thereof.
[0068] M(OR 1 ) m (R2 n-m (1)
[0069] In the above formula (1), R 1 and R 2 each independently is a monovalent organic group having 1 to 8 carbon atoms, and is preferably an alkyl group such as a methyl group or an ethyl group. M represents an n-valent metal atom such as Si, Ti, Al, or Zr. m is an integer of 1 to n. As the metal alkoxide, for example, tetraethoxysilane [Si(OC2H5)4], triisopropoxyaluminum [Al(O-iso-C3H7)3], or the like can be given. The metal alkoxide is relatively stable after hydrolysis in an aqueous solvent, and thus, tetraethoxysilane or triisopropoxyaluminum is preferred. As the hydrolyzate of the metal alkoxide, for example, silicic acid (Si(OH)4) as the hydrolyzate of tetraethoxysilane, aluminum hydroxide (Al(OH)3) as the hydrolyzate of tripropoxyaluminum, or the like can be given. They can be used in combination of a plurality of kinds.
[0070] The above composition can further contain a hydroxyl group-containing high molecular compound. As the hydroxyl group-containing high molecular compound, for example, a water-soluble polymer such as polyvinyl alcohol, polyvinylpyrrolidone, and starch can be given. From the viewpoint of barrier properties, the hydroxyl group-containing high molecular compound is preferably polyvinyl alcohol. They can be used in combination of a plurality of kinds. The content of the hydroxyl group-containing high molecular compound in the above composition is, for example, 10 to 90% by mass.
[0071] The thickness of the gas barrier coating layer is preferably 50 to 1000 nm, and preferably 100 to 500 nm. When the thickness of the gas barrier coating layer is 50 nm or more, it tends to be possible to obtain more sufficient gas barrier properties, and when it is 1000 nm or less, it tends to be possible to maintain sufficient softness.
[0072] In the case where the barrier layer 24 includes both the inorganic thin film layer and the gas barrier coating layer, the inorganic thin film layer can be formed on the surface of the first film substrate 12, and the gas barrier coating layer can be formed on the surface of the inorganic thin film layer.
[0073] (Second Embodiment)
[0074] Figure 3 is a schematic cross-sectional view of an optical barrier film according to the second embodiment of the present disclosure. Figure 3 In the second embodiment, the optical barrier film 20B includes a barrier composite layer 22a including a second film substrate 12a and a barrier layer 24a, and an optical film 10. The barrier composite layer 22a is formed on the optical film 10 via an adhesive layer 26a in such a manner that the first film substrate 12 opposes the barrier layer 24a.
[0075] The optical barrier film 20B having the barrier composite layer 22a including the second film substrate 12a through the optical barrier film 20B can achieve excellent water vapor barrier properties and oxygen barrier properties and further reduce damage to the barrier layer or the like. The material of the second film substrate 12a can be the same as the first film substrate 12. The thickness of the second film substrate 12a is preferably, for example, 5 μm or more and 50 μm or less. When the thickness of the second film substrate 12a is 5 μm or more, the strength of the second film substrate 12a is increased, and, for example, the handling of the second film substrate 12a tends to be facilitated in a back light unit manufacturing process or the like. On the other hand, when the thickness of the second film substrate 12a is 50 μm or less, a decrease in barrier properties caused by intrusion of water vapor or oxygen from the end surface of the substrate can be suppressed.
[0076] The adhesive layer 26a is formed of an adhesive or an adhesive agent. As the adhesive, an acrylic adhesive, an epoxy adhesive, a urethane adhesive, or the like can be given. The adhesive preferably contains an epoxy resin. By containing an epoxy resin in the adhesive, the adhesion of the optical film 10 to the barrier composite layer 22a can be improved. As the adhesive agent, an acrylic adhesive agent, a polyvinyl ether adhesive agent, a urethane adhesive agent, a silicone adhesive agent, a starch paste adhesive, or the like can be given. The thickness of the adhesive layer 26a is preferably 0.5 to 50 μm, more preferably 1 to 20 μm, and further preferably 2 to 6 μm. By the thickness of the adhesive layer 26a being 0.5 μm or more, the adhesion of the optical film 10 to the barrier composite layer 22a is easily obtained, and by the thickness being 50 μm or less, a more excellent gas barrier property tends to be easily obtained.
[0077] The optical barrier film 20B of the second embodiment can be obtained, for example, by forming the barrier layer 24a on the second film substrate 12a to produce the barrier composite layer 22a separately from the optical film 10, and then adhering the optical film 10 to the barrier composite layer 22a, and aging as necessary. The production method of the optical barrier film 20B of the second embodiment is not limited to the above.
[0078] (Third Embodiment)
[0079] Figure 4 is a schematic cross-sectional view of an optical barrier film according to the third embodiment of the present disclosure. Figure 4 In the third embodiment, the optical barrier film 20C has: a barrier composite layer 22a including a second film substrate 12a and a barrier layer 24a, and an optical film 10. The barrier composite layer 22a is formed on the optical film 10 via an adhesive layer 26a with the first film substrate 12 and the second film substrate 12a opposed to each other.
[0080] (Fourth Embodiment)
[0081] Figure 5is a schematic cross-sectional view of an optical barrier film according to a fourth embodiment of the present disclosure. Figure 5 In the fourth embodiment, the optical barrier film 20D has a barrier composite layer 22a including the second film substrate 12a and the barrier layer 24a, a barrier composite layer 22b including the third film substrate 12b and the barrier layer 24b, and the optical film 10. The barrier composite layer 22a is formed on the optical film 10 via the adhesive layer 26a in such a manner that the first film substrate 12 opposes the second film substrate 12a, and the barrier composite layer 22b is formed on the barrier composite layer 22a via the adhesive layer 26b in such a manner that the barrier layer 24a opposes the barrier layer 24b.
[0082] [Color conversion film]
[0083] Figure 6 is a schematic cross-sectional view of a color conversion film according to one embodiment of the present disclosure. The color conversion film is a film that can convert a part of the wavelengths of light from a light source of a backlight unit for a liquid crystal display panel. Figure 6 In the fourth embodiment, the optical barrier film 20D has a barrier composite layer 22a including the second film substrate 12a and the barrier layer 24a, a barrier composite layer 22b including the third film substrate 12b and the barrier layer 24b, and the optical film 10. The barrier composite layer 22a is formed on the optical film 10 via the adhesive layer 26a in such a manner that the first film substrate 12 opposes the second film substrate 12a, and the barrier composite layer 22b is formed on the barrier composite layer 22a via the adhesive layer 26b in such a manner that the barrier layer 24a opposes the barrier layer 24b.
[0084] By the color conversion film 30 having the concave-convex surfaces 20F and 20G on the surface, in the case where other components are stacked on the concave-convex surfaces 20F and 20G of the color conversion film 30, adhesion to the other components can be suppressed. In addition, even if the color conversion film 30 is stacked with, for example, a light guide plate that constitutes a backlight unit, the light guide plate can be prevented from being damaged by the protruding particles 18. In addition, the barrier layer itself can be prevented from being damaged, and thus, air and water vapor can be appropriately reduced from invading the color conversion layer 32, and the color conversion performance of the color conversion film 30 can be maintained for a long period of time.
[0085] The color conversion film of the present disclosure is not limited to the above-described embodiments. Figure 6 In the fourth embodiment, the color conversion film 30 is exemplified as a structure in which the color conversion layer 32 is sandwiched by two optical barrier films 20 (protective films), but one of the two protective films that sandwich the color conversion layer 32 can be an optical barrier film 20, and the other can be a protective film of another structure.
[0086] The color conversion layer 32 contains a resin and phosphors. The thickness of the color conversion layer 32 is several tens to several hundreds of μm. As the resin, for example, a photocurable resin or a thermocurable resin can be used. The color conversion layer 32 preferably contains two kinds of phosphors composed of luminescent nanocrystals (quantum dots). In addition, the color conversion layer 32 can be made of two or more layers of a phosphor layer containing one kind of phosphor and a phosphor layer containing a different kind of phosphor. The two kinds of phosphors are selected so that the excitation wavelengths are the same. The excitation wavelength is selected based on the wavelength of light irradiated from the light source of the backlight unit. The fluorescent colors of the two kinds of phosphors are different from each other. In the case where the light source is a blue light-emitting diode (blue LED), the respective fluorescent colors are red and green. The wavelengths of the respective fluorescences and the wavelength of light irradiated from the light source are selected based on the spectral characteristics of the color filter. In terms of the peak wavelength of the fluorescence, for example, 610 nm in red and 550 nm in green.
[0087] Next, the particle structure of the phosphor is described. As the phosphor, a core / shell type luminescent nanocrystal having a good luminous efficiency is particularly preferable. The core / shell type luminescent nanocrystal is manufactured, for example, from a material containing an inorganic material, preferably from a material containing an inorganic conductor or semiconductor material.
[0088] As the semiconductor material, for example, a Group II-VI, Group III-V, Group IV-VI, and Group IV semiconductor can be given. More specifically, for example, Si, Ge, Sn, Se, Te, B, C (including diamond), P, BN, BP, BAs, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, ZnO, ZnS, ZnSe, ZnTe, CdS, CdSe, CdTe, HgS, HgSe, HgTe, BeS, BeSe, BeTe, MgS, MgSe, GeS, GeSe, GeTe, SnS, SnSe, SnTe, PbO, PbS, PbSe, PbTe, CuF, CuCl, CuBr, CuI, Si3N4, Ge3N4, Al2O3, (Al, Ga, In)2(S, Se, Te)3, and Al2CO, or any combination of two or more of them can be given.
[0089] The nanocrystal may, for example, contain a dopant of p-type or n-type. In addition, the nanocrystal may, for example, contain a II-VI or III-V semiconductor. The II-VI semiconductor nanocrystal contains, for example, any combination of Group II elements such as Zn, Cd, and Hg, and Group VI elements such as S, Se, Te, and Po. The III-V semiconductor nanocrystal contains, for example, any combination of Group III elements such as B, Al, Ga, In, and Tl, and Group V elements such as N, P, As, Sb, and Bi.
[0090] The core / shell type light-emitting nanocrystal is a crystal in which a semiconductor crystal core serving as a light-emitting portion is covered with a shell serving as a protective film. For example, the core can use cadmium selenide (CdSe), and the shell can use zinc sulfide (ZnS). The surface defects of the CdSe particles are covered with ZnS having a larger band gap, and thus the quantum yield is improved. In addition, the phosphor can be a phosphor in which the core is covered with a double layer of a first shell and a second shell. In this case, the core can use CdSe, the first shell can use zinc selenide (ZnSe), and the second shell can use ZnS.
[0091] The color conversion layer 32 can have a single layer structure in which the phosphors are completely dispersed in a single layer, or can have a multilayer structure in which the respective phosphors are dispersed in a plurality of layers and stacked.
[0092] Next, the manufacturing method of the color conversion film 30 of the present embodiment will be described. As the forming method of the color conversion layer 32, there is no particular limitation, and for example, the method described in Japanese Patent Application Publication No. 2013-544018 can be cited. The phosphors are dispersed in a binder resin, the prepared phosphor dispersion liquid is applied to the surface of the optical barrier film 20 (first protective film) on the side opposite to the coating layer 14, and then another optical barrier film 20 (second protective film) is attached to the applied surface with the coating layer 14 facing the opposite side of the color conversion layer 32, and the color conversion layer 32 is cured, whereby the color conversion film 30 can be manufactured.
[0093] [Backlight unit]
[0094] Figure 7 is a schematic cross-sectional view of a backlight unit according to an embodiment of the present disclosure. Figure 7In the backlight unit 40, the light source 42, the light guide plate 46, and the color conversion film 30 disposed on the light guide plate 46 are provided. The color conversion film 30 is disposed so that the concave-convex surface 20F (i.e., the concave-convex surface 14A of the coating layer 14) of the color conversion film 30 is in contact with the light guide plate 46. Specifically, in the backlight unit 40, the light guide plate 46 and the reflection plate 44 are disposed in this order on the concave-convex surface 20F of the color conversion film 30, and the light source 42 is disposed on the side surface of the light guide plate 46 (in the direction of the surface of the light guide plate 46). The backlight unit 40 is provided with the color conversion film 30 having a sufficiently small difference in performance in the plane. Therefore, the difference in performance (color, brightness, etc.) of the backlight unit 40 can also be sufficiently small. In the backlight unit 40, damage to the light guide plate 46 in contact with the color conversion film 30 can be suppressed. In addition, damage to the barrier layer itself can also be suppressed. Therefore, the intrusion of air and water vapor into the color conversion layer can be appropriately reduced, and good white light can be obtained from the backlight unit for a long period of time.
[0095] The light guide plate 46 and the reflection plate 44 are plates that efficiently reflect and guide light emitted from the light source 42, and known materials can be used. As the light guide plate 46, for example, acrylic, polycarbonate, and a cyclic olefin film, etc. can be used. The material for the light guide plate 46 does not have a large hardness and tends to be easily damaged due to contact with other components. In particular, polycarbonate is generally used in view of high transparency and easy processing, but has a low surface hardness and is easily damaged. A plurality of blue light emitting diode elements are provided in the light source 42, for example. The light emitting diode elements can also be violet light emitting diodes, or light emitting diodes of a lower wavelength. Light emitted from the light source 42 is incident on the light guide plate 46 (in the D1 direction), and then is incident on the color conversion layer 32 (in the D2 direction) by reflection, refraction, etc. Yellow light generated in the color conversion layer 32 is mixed in the light before the color conversion layer 32, and as a result, the light that has passed through the color conversion layer 32 becomes white light.
[0096] Embodiment
[0097] Hereinafter, the application of the present disclosure will be specifically described by citing examples, but the scope of the application of the present disclosure is not limited to these.
[0098] (Used components)
[0099] In order to prepare the coating layer composition (coating liquid) of Examples 1 to 5 and Comparative Example 1, the following components were prepared.
[0100] • Main agent 1: mixture of urethane-based fine particles (average particle diameter 6.20 μm, standard deviation of particle diameter 2.25 μm) and a transparent material (manufactured by DIC Graphics Co., Ltd.)
[0101] • Main agent 2: mixed agent of urethane-based microparticles (average particle diameter 7.46 μm, standard deviation of particle diameter 13.39 μm) and transparent material (manufactured by DIC Graphics Co., Ltd.)
[0102] • Transparent material: varnish for adjusting the concentration of microparticles of main agents 1, 2 (manufactured by DIC Graphics Co., Ltd.)
[0103] • Curing agent: isocyanate curing agent (manufactured by DIC Graphics Co., Ltd.)
[0104] • Antistatic agent: Resistat PU-101 (trade name, manufactured by the First Industrial Co., Ltd.)
[0105] • Solvent: toluene (manufactured by Wako Pure Chemical Industries, Ltd., Class 1)
[0106] (Measurement of physical property values of microparticles contained in main agents 1, 2)
[0107] The "average particle diameter" and "standard deviation of particle diameter" of the microparticles contained in the main agents 1, 2 were measured as follows. That is, the main agent was put in a glass bottle, and after being vibrated 100 times, ethyl acetate was added. The average particle diameter and standard deviation of particle diameter of the microparticles contained in the thus obtained sample were measured using a laser diffraction / scattering type particle diameter distribution measuring device (Nikkiso Co., Ltd., Microtrac MT3300 (trade name)). The results are shown in Table 1.
[0108] [Table 1]
[0109] Physical properties of the microparticles contained in the main agent Main agent 1 Main agent 2 Average particle diameter 6.20 μm 7.46 μm Standard deviation of particle diameter 2.25 μm 13.39 μm
[0110] (Production of optical film)
[0111] A coating composition in which the components shown in Table 2 were mixed was applied to the first film substrate, and a coating film was formed using a wire bar coater. Next, the coating film was dried by heating at 80°C for 30 seconds. The optical films of Examples 1 to 5 and Comparative Example 1 were each produced by, after the drying of the coating film, performing aging at 60°C for two days. In Examples 1 to 5, the coating amount was changed by using wire bars of different numbers when forming the coating film of the coating composition, whereby coating layers of different thicknesses were formed on the first film substrate.
[0112] [Table 2]
[0113] Ingredients Examples 1 to 5 Comparative example 1 Main agent 1 13.52g - Main agent 2 - 13.52g Transparent material 4.62g 4.62g Curing agent 0.88g 0.88g Antistatic agent 0.64g 0.64g Solvent 10.35g 10.35g Total 30g 30g
[0114] The optical films of the above examples and comparative example were evaluated for the following items. The results are shown in Table 3.
[0115] (Haze and total light transmittance)
[0116] The haze and total transmittance of the optical films in the examples and comparative examples were measured using a haze meter (turbidity meter) NDH-2000 (trade name, manufactured by Nippon Denshoku Kogyo Co., Ltd.).
[0117] (Damage-resistant)
[0118] The optical films obtained in the examples and comparative examples were cut into 4cm × 4cm pieces. The coating of the cut optical films was then laminated onto the polycarbonate films in an interleaved manner, and the films were heated at room temperature at 25 kgf / cm². 2 The film was placed under a load for 30 seconds. Then, the optical film and polycarbonate film were observed visually and microscopically, and their damage resistance was evaluated according to the following criteria. It should be noted that the prepared polycarbonate film simulates the light guide plate of the backlight unit. The thickness of the polycarbonate film was 188 μm.
[0119] A: No damage was observed on the coating of the optical film or the polycarbonate film.
[0120] B: Damage is seen on at least one of the coating of the optical film and the polycarbonate film.
[0121] C: Significant damage is observed on at least one of the coating of the optical film and the polycarbonate film.
[0122] (Surface resistivity)
[0123] For the surface of the coating of the optical film obtained in the examples and comparative examples, a high impedance ohmmeter (trade name: Hiresta UP MCP-HT450, manufactured by DiaInstruments Co., Ltd.) was used to measure the surface resistance according to JIS-K6911 (applied voltage: 500V, time: 10 seconds, probe: URS conditions, 23°C 55%RH environment).
[0124] [Table 3]
[0125]
[0126] As shown in Table 3, the haze value of the optical film (coating thickness 4.5 μm) of Example 2 was 44.0%, while the haze value of the optical film (coating thickness 6.0 μm) of Comparative Example 1 was 40.3%, and the two values were quite close. Therefore, as described below, the haze was measured at multiple locations of the optical films of Example 2 and Comparative Example 1 to evaluate the in-plane difference in haze, and the physical property values (average particle size and standard deviation of particle size) of the particles contained in these coatings were measured.
[0127] (Evaluation of in-plane differences in haze)
[0128] A sample was prepared by cutting the optical film of Example 2 and Comparative Example 1 into a 100 mm square. The haze was measured at five points (measurement points 1 to 5) in the center and near the corners of the sample. The average value of the haze and the standard deviation of the haze were calculated from the measured values. The results are shown in Table 4.
[0129] [Table 4]
[0130]
[0131] (Measurement of physical property values of the particles contained in the coating layer)
[0132] The "average particle diameter" and the "standard deviation of the particle diameter" of the particles contained in the coating layer of the optical film of Example 2 and Comparative Example 1 were measured as follows. That is, the optical film of Example 2 and Comparative Example 1 was magnified 1000 times with an optical microscope (refer to Figure 8 (a)), and the diameters of 50 randomly selected particles were measured. As shown in Figure 8 (b), the length in the transverse direction (X) and the length in the longitudinal direction (Y) were measured, and the average value (= (X + Y) / 2) was taken as the diameter of the particle. The values of the "average particle diameter" and the "standard deviation of the particle diameter" of the particles calculated from these measured values are shown in Table 5. Note that, in the measurement of the particle diameter, the diameters of the particles were measured by the following method. Figure 8 (a) is an image displayed after magnifying the coating layer of the optical film of Example 2 with an optical microscope, Figure 8 (b) is an image displayed after further magnifying the particle surrounded by the circle in Figure 8 (a).
[0133] [Table 5]
[0134] Physical properties of the microparticles contained in the coating layer Example 2 Comparative example 1 Average particle diameter 10.1 μm 6.5 μm Standard deviation of particle diameter 2.4 μm 4.1 μm
[0135] (Measurement of the arithmetic average roughness Ra of the coating layer)
[0136] The arithmetic average roughness Ra of the coating layer of the optical film of Example 2 and Comparative Example 1 was measured. A non-contact surface layer cross-section measuring system (VertScan, Ryosan System Co., Ltd.) was used for the measurement. The results are as follows.
[0137] • Example 2: 0.27 μm
[0138] • Comparative Example 1: 0.42 μm
[0139] (Evaluation of the amount of particles detached from the coating layer)
[0140] After the surface of the coating of the optical film of Example 2 was treated by rubbing the coating against each other, the surface was magnified with an optical microscope, and within the image, the sites where the particles were removed by the above treatment were counted, and as a result, such sites were 8. The length in the transverse direction (X) and the length in the longitudinal direction (Y) of the sites were measured respectively (refer to Figure 9 ), and the average (= (X + Y) / 2) thereof was set as the diameter of the removed portion, and the area of each site was calculated. The results are shown in Table 6.
[0141] The same treatment was also performed for the coating of the optical film of Comparative Example 1, and then the surface was magnified with an optical microscope, and within the image, the sites where the particles were removed by the above treatment were counted, and as a result, such sites were 9. For these sites, the length in the transverse direction (X) and the length in the longitudinal direction (Y) were also measured respectively, and the average (= (X + Y) / 2) thereof was set as the diameter of the removed portion, and the area of each site was calculated. The results are shown in Table 7.
[0142] [Table 6]
[0143]
[0144] [Table 7]
[0145]
[0146] (Evaluation of pencil strength of coating)
[0147] A coating composition prepared by mixing the components shown in Table 8 was applied to a first film substrate having a width of 210 mm, and a coating film having a length of 300 mm was formed using a wire bar coater. Subsequently, the coating film was heated at 80°C for 30 seconds to dry the coating film. For the dried coating film, aging was performed at 60°C for two days, thereby producing the optical film of Example 6 and Comparative Example 2, respectively. In Example 6 and Comparative Example 2, the thickness of the coating formed on the first film substrate was 3 μm. Note that the same components as in Examples 1 to 5 were used in Example 6, and the same components as in Comparative Example 1 were used in Comparative Example 2.
[0148] The pencil strength of each of 12 sites of the coating of Example 6 and Comparative Example 2 was measured according to JIS K5600-5-4: 1999 "Scratch hardness (pencil method)". The load applied to the tip of the pencil was set to 500 g. The results are shown in Table 9.
[0149] [Table 8]
[0150] Ingredients Example 6 Comparative example 2 Main agent 1 Main agent 2 - Transparent material - Curing agent Antistatic agent Solvent Total 46.65 kg 50.95 kg Example 6 Comparative example 2 HB HB HB HB HB
[0151] [Table 9]
[0152] 1 2 3 4 5 6 7 8 9 10 11 12 H 2H H H H 2H 2H H H 2H H H F B B F H H H H
[0153] Industrial applicability
[0154] According to the present disclosure, an optical film having a sufficiently small in-plane difference in haze value, and an optical barrier film, a color conversion film, and a backlight unit using the same can be provided.
[0155] Symbol explanation
[0156] 10… optical film, 12… first film substrate, 14… coating layer, 14A… concavo-convex surface, 16… adhesive resin, 18… fine particles, 20A, 20B, 20C, 20D, 20… optical barrier film, 22a, 22b… barrier composite layer, 24, 24a, 24b… barrier layer, 30… color conversion film, 32… color conversion layer, 40… backlight unit.
Claims
1. An optical film, comprising: First film substrate, and The coating formed on the first membrane substrate, The coating comprises an adhesive resin and microparticles, wherein the microparticles have an average particle size of 0.5 μm to 10.0 μm and a standard deviation of particle size of 1 / 5 to less than 1 / 2 of the average particle size. Based on the total amount of the coating, the content of the microparticles in the coating is 5% to 50% by mass. The adhesive resin is a molded thermoplastic resin, or a cured thermosetting resin or a radiation-curing resin. The arithmetic mean roughness Ra of the coating is less than 0.4 μm.
2. The optical film according to claim 1, The hardness of the coating is in the range of H to 2H according to a pencil hardness tester.
3. The optical film according to claim 1 or 2, The hardness of the particles is below 100 on the Rockwell R hardness scale.
4. The optical film according to any one of claims 1 to 3, The surface resistivity of the coating is 1.0 × 10⁻⁶. 13 Below Ω / □.
5. An optical barrier film, comprising: Barrier layer, and The optical film according to any one of claims 1 to 4, The barrier layer is formed on the surface of the optical film on the side of the first film substrate.
6. An optical barrier film, comprising: A barrier composite layer comprising a second membrane substrate and a barrier layer, and The optical film according to any one of claims 1 to 4, The barrier composite layer is formed on the surface of the optical film on the side of the first film substrate.
7. The optical barrier film according to claim 5 or 6, The barrier layer comprises SiO₂ x (1.0≦x≦2.0) represents an inorganic vapor-deposited thin film layer composed of silicon oxide.
8. A color conversion film, comprising: Color conversion layer, and Two protective films are configured to sandwich the color conversion layer. At least one of the two protective films is the optical barrier film according to any one of claims 5 to 7. The optical blocking film is configured such that the coating faces the opposite side of the color conversion layer.
9. A backlight unit, comprising: light source; Light guide plate; The color conversion film of claim 8 is disposed on the light guide plate. The color conversion film is configured such that the coating is in contact with the light guide plate.
Citation Information
Patent Citations
Quantum dot film, lighting device, and lighting method
JP2013544018A